M. Dufrenne’s Conception of Aesthetic Experience - Parulskienė, Vijolė (Problemos, 1994)
The changes in aesthetic experience of the modern art are considered. The art is said to provoke the audience “to sink” into aesthetic experience. The lack of the distance between artist and audience is shown to be responsible for the phenomenon. The coexistence of the creative act is said to lead the audience up to universal humanity.